Effects of Dietary Nitrate Supplementation on Performance during Single and Repeated Bouts of Short-Duration High-Intensity Exercise: A Systematic Review and Meta-Analysis of Randomised Controlled Trials - Nehal S. Alsharif; Tom Clifford; Abrar Alhebshi; Samantha N. Rowland; Stephen J. Bailey (MDPI AG, 2023)
Inorganic nitrate (NO3−) has emerged as a potential ergogenic aid over the last couple of decades. While recent systematic reviews and meta-analyses have suggested some small positive effects of NO3− supplementation on performance across a range of exercise tasks, the effect of NO3− supplementation on performance during single and repeated bouts of short-duration, high-intensity exercise is unclear. This review was conducted following PRISMA guidelines. MEDLINE and SPORTDiscus were searched from inception to January 2023. A paired analysis model for cross-over trials was incorporated to perform a random effects meta-analysis for each performance outcome and to generate standardized mean differences (SMD) between the NO3− and placebo supplementation conditions. The systematic review and meta-analysis included 27 and 23 studies, respectively. Time to reach peak power (SMD: 0.75, p = 0.02), mean power output (SMD: 0.20, p = 0.02), and total distance covered in the Yo-Yo intermittent recovery level 1 test (SMD: 0.17, p < 0.0001) were all improved after NO3− supplementation. Dietary NO3− supplementation had small positive effects on some performance outcomes during single and repeated bouts of high-intensity exercise. Therefore, athletes competing in sports requiring single or repeated bouts of high-intensity exercise may benefit from NO3− supplementation.